Model of Biomineralization of Ferrum Compounds by Gallionella Cells Immobilized on Contact Loading of Bioreactor - Oleksandr Kvartenko; Iryna Gryuk; Larysa Sablii (Energy Engineering and Control Systems)
In the underground waters not polluted by organic compounds the bivalent iron occurs in the form of hydrocarbonates. An inseparable part of ferrum ions are ferrum bacteria. As a result of the literature review carried out it is determined that up till present no mechanism of the impact of additional source of non-organic carbon on the processes of in-cellular metabolism of Gallionella type bacteria had been established. The aim of the paper is the determination of the effect of the additional source of non-organic carbon in the form of Na2CO3 on processes of metabolism and the rate of biochemical oxidation of iron compounds by bacteria Gallionella sp. and the development of the possible mechanism of the assimilation of non-organic carbon in the recovered pentose phosphate cycle. The comprehensive scheme of activating bacteria metabolism developed by us testifies to the possibility of increasing the energy capacity of recovered pentose phosphate cycle, the acceleration of metabolism cycles and the rate of pumping electrons via the fermentative cell system. The totality of presented processes results in speeding up the fermentative oxidation of Fe2+ on the surface of a cell with the final formation of matrix structures of biominerals and the increased efficiency of bioreactors operation.